Game Pembelajaran Fisika Dengan Game Bertipe Adventure Game - Andrew Victory Walelang; Liliana Liliana; Gregorius Satia Budhi (Jurnal Infra, 2015)
Game is an entertainment media this is growing rapidly along with the development of technology. Adventure Game is a game that is more concerned with the storyline and moral message for the players. Physics is one of the lessons that discusses the natural phenomena that are not live or matter within the scope of space and time. Physics lessons started in junior high school education. In the eighth grade junior high school, there was a discussant physics lesson on Force, Acceleration, Work and Energy that are hard to explain without media.Therefore, in this thesis, author developed a game that can help students in grade 8 junior to study about Force, Acceleration, Work, and Energy with ease. This game is created using Unity. Unity is one of the media to create a game with 3D and 2D. The programming language used by Unity are C# and Javascript.Results obtained from surveys to students in grade 8 junior on this physics game can be summed adventure game Physics 85% interested, 70% in accordance with the lessons 8 junior class , 70% of the questions easy to understand, and 65% of the questions that are given can help the learning process of students in grade 8 junior well.